1992
DOI: 10.2190/b9pc-51rj-1d7n-4m94
|View full text |Cite
|
Sign up to set email alerts
|

Imagined Interaction, Conversational Sensitivity and Communication Competence

Abstract: This research explores the relationship between imagined interaction dimensions [1], conversational sensitivity dimensions [2], and communication competence [3]. Results of a study reveal features of imagined interaction predicting both conversational sensitivity and self-reported communication competence. Mental experiences of communication (i.e., imagined interaction) are thought to activate sensitivity to conversations and to provide knowledge structures for competent interaction. A path analysis revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Communication reinforces negative emotions in unhappy marriages and accents positive affect in happy marriages. Unhappy couples use fewer positive behaviors and more negative behaviors than do happy couples (Krokoff, Gottman, & Hass, 1989). Although these conclusions may seem mundane, they are more counterintuitive when they also apply to innocuous discussion of events of the day, as opposed to discussing major complaints in the marriage.…”
Section: Functions Of Talkmentioning
confidence: 99%
“…Communication reinforces negative emotions in unhappy marriages and accents positive affect in happy marriages. Unhappy couples use fewer positive behaviors and more negative behaviors than do happy couples (Krokoff, Gottman, & Hass, 1989). Although these conclusions may seem mundane, they are more counterintuitive when they also apply to innocuous discussion of events of the day, as opposed to discussing major complaints in the marriage.…”
Section: Functions Of Talkmentioning
confidence: 99%
“…Confirmatory factor analysis (CFA) has continued to support the dimensions of IIs that were originally identified in earlier studies (Honeycutt et al, 1989, 1992). They reported eight characteristics (frequency, dominance, valence, discrepancy, proactivity, retroactivity, variety, specificity).…”
Section: Methodsmentioning
confidence: 80%
“…II valence was also positively correlated with II frequency for the Thai and American participants. Given that research informs us that chronically lonely individuals lack II frequency (Honeycutt et al, 1989) and that pleasant IIs can elicit positive moods whereas negative IIs can bring forth negative affect (Honeycutt et al, 1992), it would seem that frequent interaction with (significant) others may have a significant role to play in promoting positive mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specificity aids in greater recall of the II and can contain visual (scene of the II) and verbal imagery including descriptive contexts and distinct wording. Observations reported by Honeycutt, Zagacki, and Edwards (1993) revealed that the level of detail in IIs positively predicted several dimensions of conversational sensitivity including the ability to detect meanings in another's messages, conversational memory and Procedure. The sample was randomly divided into the rehearsal and no rehearsal groups.…”
Section: Rehearsal and Specificity In Verbal Fluency And Camentioning
confidence: 99%